Design of a Smart Farming Monitoring System Leveraging Internet of Things Technology: Application of the NPKTHCPH -S Sensor - Freddy Artadima Silaban; Yustisi Ayunda Putri; Sicilia Riris Oktaviany (UNIVERSITAS RAHARJA, 2024)
Shallot plants are currently widely cultivated, but cultivation is still done manually to control soil conditions. For this reason, with a monitoring system using the NPKTHCPH-S sensor, which can show seven parameters of soil conditions using only one sensor, it is hoped that it will make it easier to see the appropriate soil content and required shallot plants according to the criteria for good shallot plant growth, so that plant growth shallots become more optimal and avoid crop failure. The smart farming monitoring system prototype uses the NPKTHCPH-S sensor, which was developed using the Blynk application by implementing several components such as the NPKTHCPH-S sensor, ESP32, Relay 3.3, RS485-TTL Converter. The NPKTHCPH-S sensor is a reader of soil water content, electrical conductivity, temperature, nitrogen, phosphorus, potassium, and pH in shallot soil. The results obtained from the NPKTHCPH-S sensor test were the most significant seen at 2 pm found a temperature value of 35.6oC with a humidity of 50.7%. And at 11 pm it was found that the temperature was 28.4oC with a humidity of 58.6%. The values ​​for N, P, K, and Conductivity were constant for 9 hours of testing, namely for N was 170mg/kg, for P was 439mg/k, for K was 434mg/k, and conductivity was 1000uS/cm.